Manajemen Webinar Terintegrasi Berbasis Web dan Pengembangan Sistem Perpustakaan Digital untuk Divisi Pelatihan SDM - Rizal Dewo Susanto; Toni Wijanarko Adi Putra; Eko Siswanto (Pusat Riset dan Inovasi Nasional, 2026)
The rapid growth of digital technology has transformed how organizations manage human resource training. PT Bisnis Digital Ekonomi (BDE), through its HR Master Division, conducted 16 webinar series with 2,851 participants between July 2025 and February 2026; however, all administrative processes were managed manually across disconnected platforms including Zoom, Google Drive, and spreadsheets, resulting in fragmented knowledge assets and operational inefficiency. This study aims to design and develop an integrated web-based webinar management and Digital Library system for the HR Master Division using the Waterfall method. Data were collected through direct observation and semi-structured interviews with two division staff members. The system was built using PHP Laravel with MVC architecture and MySQL database, supporting four user roles: Super Admin, HR Master Admin, Trainer, and Employee. Black Box Testing across 24 test scenarios yielded a 100% success rate with no critical bugs detected. The system successfully consolidates webinar scheduling, participant registration, digital attendance, material archiving, and report export into a single platform accessible via hrmasterid.com, eliminating cross-platform fragmentation. This study contributes a replicable integrated training information system model for corporate HR divisions facing similar knowledge management challenges.